Vivencias emocionales en adolescentes wayuu con embarazo entre 14 - 16 años, Barrio Brisas del Mar de Riohacha (2023)
The objective of this research project is to analyze the experiences emotions in Wayuu adolescents with pregnancy between 14 - 16 years old, Brisas del Mar neighborhood of Riohacha, a situation that has been presenting a series of social, psychological and physical in adolescents in that sector. The central problem of the research is made up of a series of factors affecting Wayuu adolescents, a product of the biographical rupture from the factual fact and in the different phases of the investigation they showed, among others, what following: insecurity when speaking, transformation of their routine, disagreements with their families, lack of job opportunity, school dropout; In the same way, the series of deficiencies is described and affections to which they are subjected by elements of their own families as well as the rejection of it and its social environment, risking the mental and physical health of this age group.